1988
DOI: 10.1002/bin.2360030304
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a problem‐solving strategy to closed head‐injured adults

Abstract: A m a . IlIino is 62 90 6 NANCY E. MARCHAND-MARTELLA DEBRA BRAUNLING-MCMORROWThis study developed and evaluated a program for teaching a problemsolving strategy to closed head-injured adults. Four general areas were targeted for training: Community Awareness and Transportation; Medication, Alcohol, and Drugs; Stating One's Rights; and Emergencies, Injuries, and Safety. The program featured cue cards, response-specific feedback, modeling, self-monitoring, positive reinforcement, response practice, self-correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In their excellent review, Tisdelle and St. Lawrence (1986) suggested that training programs need to begin empirically demonstrating the relevance of the program's skill objectives instead of simply relying on clinical intuition as has been past practice. The social validity procedures employed here and in our previous research (Foxx et al, 1988;Foxx et al, 1989) appear to offer one such way of identifying those skill components or processes that do represent actual problem solving and hence that should be taught. Consider that the targeted components or processes ("Where would you look for help"?, "Who would you talk to"?, and "What would you say"?)…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In their excellent review, Tisdelle and St. Lawrence (1986) suggested that training programs need to begin empirically demonstrating the relevance of the program's skill objectives instead of simply relying on clinical intuition as has been past practice. The social validity procedures employed here and in our previous research (Foxx et al, 1988;Foxx et al, 1989) appear to offer one such way of identifying those skill components or processes that do represent actual problem solving and hence that should be taught. Consider that the targeted components or processes ("Where would you look for help"?, "Who would you talk to"?, and "What would you say"?)…”
Section: Discussionmentioning
confidence: 89%
“…One, it increased the likelihood that the students would attend to each other's responses and feedback since they were required to respond to all of the situations each session by providing either an initial solution or an alternative one. This led to increased interaction among them since they frequently gave each other corrective and positive feedback and kept them from becoming bored or inattentive (see Foxx et al, 1988). This requirement also enhanced the effects of response practice since they had more opportunities to rehearse a strategy for each problem situation which may have reduced their errors, helped them retain new material (see Kent-Udolf, 1984), and acquire the strategy quickly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations